2017
DOI: 10.3892/etm.2017.5272
|View full text |Cite
|
Sign up to set email alerts
|

An in�vitro endothelial cell protective effect of secretory leukocyte protease inhibitor against simulated ischaemia/reperfusion injury

Abstract: Endothelial dysfunction is an essential deleterious modulator of ischaemia/reperfusion (I/R) injury. Secretory leukocyte protease inhibitor (SLPI) has demonstrated myocardial protection in cardiac transplantation; however, the effect of SLPI in endothelial I/R injury remains unexplored. In the present study, the effect of recombinant human SLPI (rhSLPI) treatment against endothelial cells (ECs) subjected to simulated I/R injury and the effect of treatment at different time points were determined. Human umbilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…The current study hypothesized that endothelial-derived rhSLPI could prime the cardiomyocytes and enhance the cardioprotective effect on cardiac cells subjected to in vitro I/R injury. The findings from the current study showed that endothelial-derived rhSLPI showed a greater protective effect than that found using recombinant human SLPI in our previous studies on cardiac resident cells [11,12,13,14].…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…The current study hypothesized that endothelial-derived rhSLPI could prime the cardiomyocytes and enhance the cardioprotective effect on cardiac cells subjected to in vitro I/R injury. The findings from the current study showed that endothelial-derived rhSLPI showed a greater protective effect than that found using recombinant human SLPI in our previous studies on cardiac resident cells [11,12,13,14].…”
Section: Discussioncontrasting
confidence: 44%
“…Previous studies reported that SLPI acts as an ROS scavenger by reducing intracellular ROS production in many cells during sI/R [11,12,13,14]. To prove that SLPI secreted from EA-SLPI cells reduced intracellular ROS production, in vitro intracellular ROS production was determined under simulated ischemia (sI), hypoxia, and H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…such as acute lung injury 9,10 . In the setting of oxidative stress, SLPI seems to have antioxidant and cytoprotective properties 11,12 . In a murine model of experimental ischemic AKI, Macrophage Migration Inhibitory Factor-2 (MIF-2) was suggested to exert kidney protection by upregulation of SLPI expression 13 .…”
mentioning
confidence: 99%